2009
DOI: 10.1002/elan.200804521
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of DNA‐Reactive Metabolites from Nitrosamine and Styrene Using Voltammetric DNA/Microsomes Sensors

Abstract: Voltammetric sensors made with films of polyions, double-stranded DNA and liver microsomes adsorbed layer-by-layer onto pyrolytic graphite electrodes were evaluated for reactive metabolite screening. This approach features simple, inexpensive screening without enzyme purification for applications in drug or environmental chemical development. Cytochrome P450 enzymes (CYPs) in the liver microsomes were activated by an NADPH regenerating system or by electrolysis to metabolize model carcinogenic compounds nitros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…A dense coverage with a distribution of circular well-like structures of variable size was found, with a 2-fold increase in surface roughness over the underlying layer. Microsomes create these well-like vesicular features by partially flattening on surfaces, as concluded from previous electron microscopy and AFM studies. , The horizontal diameter of the circular structures was 141 ± 35 nm, and the vertical height was 12 ± 5 nm. Electron microscopy on RLMs revealed similar circular features with variable diameters of 80–400 nm …”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…A dense coverage with a distribution of circular well-like structures of variable size was found, with a 2-fold increase in surface roughness over the underlying layer. Microsomes create these well-like vesicular features by partially flattening on surfaces, as concluded from previous electron microscopy and AFM studies. , The horizontal diameter of the circular structures was 141 ± 35 nm, and the vertical height was 12 ± 5 nm. Electron microscopy on RLMs revealed similar circular features with variable diameters of 80–400 nm …”
Section: Resultssupporting
confidence: 67%
“…Microsomes create these well-like vesicular features by partially flattening on surfaces, as concluded from previous electron microscopy and AFM studies. 41,42 The horizontal diameter of the circular structures was 141 ( 35 nm, and the vertical height was 12 ( 5 nm. Electron microscopy on RLMs revealed similar circular features with variable diameters of 80À400 nm.…”
Section: ' Resultsmentioning
confidence: 99%
“…Rusling’s group developed an interesting approach for monitoring reactive metabolites by employing electrodes coated with cytochrome P450/DNA films prepared using a layer-by-layer technique. In these sensors, enzyme reaction produced metabolites and the resulting DNA damage was detected by either voltammetry using soluble [Ru­(bipy) 3 ] 2+ catalyst (regenerated by A and G residues in damaged DNA), , or with single electrode ECL , and ECL arrays. , The required films could be placed on a single PGE, ,, in a block array format, or on silica nanoparticles for LC-MS analysis . Studies performed on these formats included the metabolism and genotoxicity of styrene, benzo­[a]­pyrene, N -nitrosamines, , and the genotoxicity of arylamines activated by N-acetyltransferase …”
Section: Detection Of Dna Damagementioning
confidence: 99%
“…Amperometric determination of N -nitrosamine at ruthenium-based polymer modified electrodes, enhanced voltammetric stripping analysis of N -nitrosamine at sulfopolyester-modified electrodes, and electrochemical detection of NDPhA using poly­(diallyldimethylammonium chloride) stabilized graphene/platinum nanoparticles have been reported and are sensitive analytical methods for N -nitrosamine detection. Furthermore, DNA adsorbed pyrolytic graphene electrodes were also used to determine N -nitrosamine . All of these have demonstrated that modified electrodes can be used in the development of N -nitrosamine sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, DNA adsorbed pyrolytic graphene electrodes were also used to determine N-nitrosamine. 12 All of these have demonstrated that modified electrodes can be used in the development of N-nitrosamine sensors. Use of DNA in the sensing field has also increased the opportunities leading to various sensing strategies.…”
Section: ■ Introductionmentioning
confidence: 99%